Проблема травматизму в кіокушин карате - Є.А. Стрикаленко; В.М. Гузар; О.Г. Шалар (H.S. Skovoroda Kharkiv National Pedagogical University, 2016)
Анотація. У статті проаналізовані результати опитування спортсменів та тренерів щодо проблеми травматизму в кіокушин карате. Найбільш характерними травмами в процесі тренувань або змагань в кіокушин карате є: розтягнення (33%); вибиття пальців (28%); забиття грудної клітки (14%); забиття стегна (12%); переломи (10%); струс мозку (3%). Були розроблені і ефективно застосовані засоби профілактики травматизму серед каратистів. Ключові слова: кіокушин карате, спортсмени, тренери, травми, лікування, профілактика. Аннотация. В статье проанализированы результаты опроса спортсменов и тренеров по проблеме травматизма в киокушин каратэ. Наиболее характерными травмами в процессе тренировок или соревнований в киокушин каратэ являются: растяжение (33%); выбивание пальцев (28%); ушиб грудной клетки (14%); ушибы бедра (12%); переломы (10%); сотрясение мозга (3%). Были разработаны и эффективно применены средства профилактики травматизма среди каратистов. Ключевые слова: киокушин каратэ, спортсмены, тренеры, травмы, лечение, профилактика. Annotation. The article analyzes the results of a survey of athletes and coaches on the problem of injuries in Kyokushin karate. The most typical injuries in the process of training and competitions in Kyokushin karate are: a sprain (33%); the ejection fingers (28%); contusion of the chest (14%); contusions to the hip (12%); fractures (10%); concussion (3%). Was developed and effectively applied means of prevention of injuries among karate. Key words: Kyokushin karate, athletes, coaches, injuries, treatment, prevention.